2017
DOI: 10.1080/01419870.2017.1367021
|View full text |Cite
|
Sign up to set email alerts
|

Public attitudes towards support for migrants: the importance of perceived voluntary and involuntary migration

Abstract: Immigration leads to strong and polarized public and political debates in Europe and the Western world more generally. In some of these debates, migrants are described as either having little choice but to migrate (involuntary) or as migrating out of their own free choice (voluntary). In two studies and using a social psychological perspective, native Dutch respondents were asked about their support for policies aimed at cultural rights and public assistance to perceived voluntary and involuntary migrants. Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 51 publications
(57 reference statements)
1
43
0
4
Order By: Relevance
“…During that time, Europe has seen political upheavals over how to respond to this influx with strong debates in all societies, including the Netherlands where the current research was conducted (Harteveld, Schaper, De Lange, & Van Der Brug, ). In this polarized debate, some people emphasize the need to support these newcomers and criticize the lack of hospitality and humanitarianism, while others favour border closure and claim that the newcomers are ‘fortune seekers’ who endanger the stability of society (Van Prooijen, Krouwel, & Emmer, ; Verkuyten, Mepham, & Kros, ). Research has found that openness to critical messages about one’s own group may turn not on the content of the message but on the identity of the critic (Hornsey, Oppes, & Svensson, ; Jetten & Hornsey, ), with an external group critic being perceived more negatively and their message being more rejected.…”
Section: Introductionmentioning
confidence: 99%
“…During that time, Europe has seen political upheavals over how to respond to this influx with strong debates in all societies, including the Netherlands where the current research was conducted (Harteveld, Schaper, De Lange, & Van Der Brug, ). In this polarized debate, some people emphasize the need to support these newcomers and criticize the lack of hospitality and humanitarianism, while others favour border closure and claim that the newcomers are ‘fortune seekers’ who endanger the stability of society (Van Prooijen, Krouwel, & Emmer, ; Verkuyten, Mepham, & Kros, ). Research has found that openness to critical messages about one’s own group may turn not on the content of the message but on the identity of the critic (Hornsey, Oppes, & Svensson, ; Jetten & Hornsey, ), with an external group critic being perceived more negatively and their message being more rejected.…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that British people generally hold more favorable attitudes toward immigration from Western European countries than Eastern European countries (e.g., Blinder, ; Ford, ). Support for polices aimed at cultural rights and public assistance has also been shown to depend on whether migration is perceived to be voluntary or involuntary (Verkuyten, Mepham, & Kros, ). Future research should consider whether such conditions may moderate the impact of intergroup contact on willingness to engage in solidarity‐based collective action, including the extent to which the disadvantaged group is perceived to pose an economic or symbolic threat to one’s ingroup (Stephan & Stephan, ).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Stále prebieha diskusia o vhodnom pomenovaní migrantov (utečenci; ne/dobrovoľní, i/legálni migranti), kde podľa dohody OSN, pojem migrant pokrýva všetky prípady, kde rozhodnutie migrovať bolo prijaté slobodne daným jednotlivcom. Pojem zahŕňa heterogénne kategórie vo verejných a politických debatách (Moses, 2006;Verkuyten, Mepham & Kros, 2018). Podľa výsledkov reprezentatívneho výskumu IOM o postojoch verejnosti k zahraničnej migrácii a migrantom v Slovenskej republike, majú obyvatelia Slovenska relatívne málo osobných skúseností s migrantmi a majú málo znalostí o migrantoch, ktoré si často vytvárajú podľa informácií z médií.…”
Section: Otázkyunclassified
“…Tieto presvedčenia majú negatívny dopad na postoje voči migrantom, nie len na teoretickej úrovni, ale aj na behaviorálnej -ide napríklad o extrémne pravicové strany mobilizujúce občanov v otázkach azylu, útoky na azylové centrá, čiastočné uzavretie Schengenských hraníc, etnocentrizmus, marginalizácia, segregácia a pod. (Moses, 2006;Verkuyten et al, 2018).…”
Section: Otázkyunclassified